Unveiling Insurance and Risk Management Insights Through Bibliometric and Cluster Analysis - Sardana, Varda; Mohapatra, Amiya Kumar; Singh, Amit Kumar; Singhania, Shubham (Prabandhan: Indian Journal of Management, 2023)
Purpose : This study aimed to identify the intellectual developments in the domain of insurance and risk management for 52 years, spanning 1971 to 2022, through a bibliometric and cluster analysis. Methodology : A total of 1,740 relevant research documents were retrieved from the Scopus database after applying pre-specified inclusion criteria. Using VOSViewer, techniques such as trend analysis, citation analysis, co-citation analysis, and keyword co-occurrence analysis were employed for performance analysis and scientific mapping. Findings : The findings highlighted the temporal and spatial trend of publications, the most productive countries, journals, authors, and seminal articles, as well as the six major themes that have been studied in this domain. It also presented the emerging themes and outlined those that can be explored in future research. This study integrated the concept of risk management in the context of insurance to determine the developments and emerging themes in this area in the past five decades. Practical Implications : From the managerial point of view, the study would help insurance companies comprehend the dynamics of risk management and would facilitate the regulators in formulating policies for better risk management and control. Originality : To the best of our knowledge, this study is the first of its kind that undertakes a comprehensive bibliometric review to understand the research landscape of insurance and risk management. However, the study has certain limitations, including the reliance on a single database (Scopus) and certain shortcomings in the bibliometric technique itself.